Digital Based Decision Formation Model in Indonesia with a Theory Planned Behavior Approach: Empirical Evidence of BSI Mobile Banking - Tahir, Atika; Rasbi, Muhammad; Ruslan, M; Wardi, Fithriah (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2024)
This study aims to explore the psychological and behavioral factors influencing digital infaq decision-making among Indonesian users of BSI Mobile Banking, using the Theory of Planned Behavior (TPB) framework. Employing a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were gathered from 115 purposively selected respondents. The findings confirm that attitudes, subjective norms, and perceived behavioral control significantly shape behavioral intention, which in turn strongly predicts digital infaq decisions. Among these, perceived behavioral control exhibits the most substantial influence on intention. Notably, intention fully mediates the relationship between psychological antecedents and actual decisions. This study contributes to global scholarship on digital Islamic finance by empirically validating the TPB model in the context of faith-driven financial behavior in emerging economies. It highlights the growing role of digital trust, user confidence, and social influence in shaping online charitable practices. The research offers practical implications for Islamic financial institutions to enhance user engagement by improving digital literacy, platform usability, and trust-building mechanisms. Future research should consider broader samples, incorporate variables such as risk perception and digital ethics, and conduct cross-national comparisons to assess the generalizability of the digital infaq decision-making model.